Law on social insurance - The National Assembly (2006)
This Law provides for social insurance regimes and policies; the rights and responsibilities of insured laborers, agencies, organizations and individuals; social insurance organizations; social insurance funds; procedures for implementation of social insurance and state management of social insurance. Law does not apply to health insurance, deposit insurance and types of business insurance.